From inclusion to peace: A journey through educational strategies and experiences - Valdés Cuervo, Ángel Alberto (Emerging Trends in Education, 2026)
The book is a valuable contribution to research and educational practice on inclusion, peaceful coexistence, and building a culture of peace. Throughout its chapters, and based on various methodological approaches, key topics are addressed, such as prosocial behavior toward peers, interventions in defense of victims of bullying and cyberbullying, as well as aspects related to the educational inclusion of students with disabilities and indigenous students at different levels of the school system. The diversity of conceptual and methodological perspectives that underpin the chapters offers a wide range of opportunities for generating new knowledge and designing effective educational interventions. In short, this text provides an understanding of the influence of multiple factors on the processes of inclusion and coexistence in schools, while highlighting the effects of various strategies aimed at promoting peace and equity in educational environments. It is therefore a highly relevant resource for both researchers and education professionals committed to inclusion and the consolidation of a culture of peace.